The Efficacy of Workplace Spirituality and Work Discipline on Employee Performance: Understanding the Mediating Role of Work Motivation - Kamila, Putri Muhtarisa Sahda; setiani, setiani; Ekowati, Vivin Maharani; Vania, Amelindha (Relevance: Journal of Management and Business, 2024)
This study aimed to test and analyze the effect of workplace spirituality and work discipline on employee performance, with work motivation as a mediating variable. This study uses quantitative methods involving a population of all Tulungagung Regency Environmental Service employees. The survey was conducted using the Non-Probability Sampling method for 98 employees. The data were processed using SmartPLS version 4.0 with validity, reliability, and hypothesis testing. The results showed that workplace spirituality did not significantly affect employee performance, and work discipline did not considerably affect employee performance. Furthermore, work motivation affects employee performance. Work Motivation can also mediate the relationship between Employee Performance and Workplace Spirituality. In addition, Work motivation can also mediate the effect of Work Discipline on Employee Performance on employees of the Tulungagung Environmental Service. This research implies that focusing on Spirituality in the workplace can improve employees' emotional and psychological well-being, which can increase job satisfaction and loyalty to the organization.